2004
DOI: 10.1056/nejm200407293510522
|View full text |Cite
|
Sign up to set email alerts
|

Transient Improvement of Spinocerebellar Ataxia with Zolpidem

Abstract: to the editor: There is currently no effective pharmacologic treatment for spinocerebellar ataxia. We describe a family of five patients, four of whom had clinical improvement within one hour after the ingestion of zolpidem (10 mg). The diagnosis of spinocerebellar ataxia type 2 was confirmed by molecular analysis. Analysis of DNA for CAG repeat expansions in the SCA1 , 2 , 3 , 6 , and 7 genes revealed expansion of CAG repeats at the SCA2 locus.Patient 1, a 49-year-old man with titubation, dizziness, and loss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 3 publications
1
30
0
Order By: Relevance
“…Subsequent perfusion testing with radiolabelled isotopes showed improved areas of hypoactivity with improved perfusion after zolpidem [8]. Further case reports have been pupblished in blepharospasm, spinocerebellar ataxia and aphasia after stroke where SPECT imaging showed a 40% increase in regional blood flow in Broca's area, left middle frontal and supramarginal gyri and bilateral orbitofrontal cortex [9][10][11]. Zopiclone, a drug in the same class, has also been reported to have the same effect [12].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent perfusion testing with radiolabelled isotopes showed improved areas of hypoactivity with improved perfusion after zolpidem [8]. Further case reports have been pupblished in blepharospasm, spinocerebellar ataxia and aphasia after stroke where SPECT imaging showed a 40% increase in regional blood flow in Broca's area, left middle frontal and supramarginal gyri and bilateral orbitofrontal cortex [9][10][11]. Zopiclone, a drug in the same class, has also been reported to have the same effect [12].…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact pathophysiologic mechanism beneath this paradoxic effect is not known. Some authors have suggested that the effects of zolpidem might be associated with the diaschisis phenomenon (16,17,18). Studies using single-photon emission computed tomography, positron emission tomography, and EEG following zolpidem therapy have reported changes in brain activity (prefrontal cortex, thalamus and striatum) (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Idebenone is more effective than the placebo for halting and reversing the hypertrophic cardiomyopathy associated with Friedreich’s ataxia [25]. Transient improvement in cerebellar symptoms upon treatment with zolpidem was observed in 4 out of 5 family members with spinocerebellar ataxia type 2 [26]. The potential effectiveness of riluzole in symptomatic therapy for diverse forms of cerebellar ataxia was noted in a pilot clinical trial [18].…”
Section: Discussionmentioning
confidence: 99%